2010
DOI: 10.1002/adfm.200901890
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(4‐vinylpyridine) Thin Films by Initiated Chemical Vapor Deposition (iCVD) for Selective Nanotrench‐Based Sensing of Nitroaromatics

Abstract: A new nanoscale sensing concept for the detection of nitroaromatic explosives is described. The design consists of nitroaromatic‐selective polymeric layers deposited inside microfabricated trenches. As the layers are exposed to nitroaromatic vapors, they swell and contact each other to close an electrical circuit. The nitroaromatic selective polymer, poly(4‐vinylpyridine) (P4VP), is deposited in the trenches using initiated chemical vapor deposition (iCVD). P4VP is characterized for the first time as a selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 30 publications
0
67
0
Order By: Relevance
“…There are many polymers which expand in response to a specifi c chemical, or class of chemicals, which would allow for the detection of analytes as diverse as alcohols, using poly(methyl methacrylate) as the spacer, [ 53 ] to nitroaromatic explosives such as TNT using poly(4-vinylpyridine). [ 60 ] To conclude, in this report we have demonstrated the operation of the nanopatch antenna system as a novel, sub-wavelength optical humidity sensor and explored the limits of its sensitivity. We have shown that by using Nafi on, a polymer that expands with increasing humidity, as the spacer layer between a silver nanocube and silver sheet we can produce a nanoscale sensor with a fast response time and higher sensitivity than any other single-particle plasmonic humidity sensor recorded.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 95%
“…There are many polymers which expand in response to a specifi c chemical, or class of chemicals, which would allow for the detection of analytes as diverse as alcohols, using poly(methyl methacrylate) as the spacer, [ 53 ] to nitroaromatic explosives such as TNT using poly(4-vinylpyridine). [ 60 ] To conclude, in this report we have demonstrated the operation of the nanopatch antenna system as a novel, sub-wavelength optical humidity sensor and explored the limits of its sensitivity. We have shown that by using Nafi on, a polymer that expands with increasing humidity, as the spacer layer between a silver nanocube and silver sheet we can produce a nanoscale sensor with a fast response time and higher sensitivity than any other single-particle plasmonic humidity sensor recorded.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 95%
“…Similarly, P4VP is produced by the thermally initiated free radical polymerization of 4-vinylpyridine. Coatings based on P4VP have been investigated for applications such as corrosion inhibition [18], humidity sensors [19], nitroaromatic sensors [10], and as a copolymer gel electrolyte in DSSCs [20].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of iCVD include its lower temperature of operation compared to other hot wire CVD techniques as well as the relative chemical purity and physical uniformity of polymer films produced on surfaces. It is a proven technique for numerous applications, including hydrogels [7][8][9], solar cells [6], sensors [10], and various thin film coatings. Compared with other film deposition techniques, like spin coating, iCVD does not use liquid solvents during processing.…”
Section: Introductionmentioning
confidence: 99%
“…17 Prieto and co-workers electrodeposited polyethyleneoxide-based films through the electroreduction of a diazonium group; the resulting films were grafted to the electrode surface and displayed electronic conductivity of 10 À10 S cm À1 , but the o10 nm thickness will limit the operating voltage when functioning as a solid-state electrolyte. 26,27 Gleason and Dunn recently explored the use of Li + -impregnated iCVD-derived polymer coatings at 2D indium-tin oxide substrates as nanoscale solid-state electrolytes. One exception is initiated chemical vapour deposition (iCVD), [20][21][22] a technique based on free-radical polymerization in which the desired monomer, typically containing vinyl moieties, and an initiating species (e.g., tert-butylperoxide) are introduced in vapour form to the desired substrate.…”
Section: Introductionmentioning
confidence: 99%